2021
DOI: 10.1007/s10668-021-01313-3
|View full text |Cite
|
Sign up to set email alerts
|

Does ecotourism in a Mangrove area at Klong Kone, Thailand, conform to sustainable tourism? A case study using SWOT and DPSIR

Abstract: This study aimed to assess ecotourism in a mangrove area and whether it conformed with sustainable tourism. We were interested in exploring the demand for natural resources and the supply of areas for ecotourism. To achieve this, we integrated a SWOT (strengths, weaknesses, opportunities, and threats) analysis with the DPSIR (driving forces, pressures, states, impacts, and responses) framework, based on questionnaire interviews with three target groups (tourists, homestay operators, and community residents), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 63 publications
(79 reference statements)
0
24
0
2
Order By: Relevance
“…Hence, SET evaluates effective policy and management regarding tourism development influenced by exchange interaction. Accordingly, the extant literature is abundant in studies reliant on SET and its link to other concepts, such as communal support of tourism [57], communal participation, and empowerment [52,58], community involvement [11], tourism policy, residents' attitude, and environmental sustainability [59], sustainability practices and policy adoption [60], environmentally responsible behavior [19], and host-tourist interaction [61].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, SET evaluates effective policy and management regarding tourism development influenced by exchange interaction. Accordingly, the extant literature is abundant in studies reliant on SET and its link to other concepts, such as communal support of tourism [57], communal participation, and empowerment [52,58], community involvement [11], tourism policy, residents' attitude, and environmental sustainability [59], sustainability practices and policy adoption [60], environmentally responsible behavior [19], and host-tourist interaction [61].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, tourism should protect sociocultural values, customs, natural heritage, and society of tourism destinations against degradation impact [58,81]. Therefore, a tourismreliant economy should develop sustainable tourism to meet residents' needs.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…alba , is required. There were more demands on ES in this area in terms of ecotourism activities ( Swangjang and Kornpiphat, 2021 ) than in L1 and L2. The SC stock of the seaside area was lower than that in L2 due to natural factors relating to the soil texture.…”
Section: Resultsmentioning
confidence: 94%
“…R. apiculata was mostly found in both land use types found of plot 3. The location of plot 3 was close to where ecotourism activities took place ( Swangjang and Kornpiphat, 2021 ). These activities included planting mangrove trees, which mostly comprised R. apiculata .…”
Section: Resultsmentioning
confidence: 99%
“…Tourism industry has witnessed noticeable growth worldwide due to the economic growth and subsequent improvement of the quality of people's life (Cui et al, 2016;Dwyer et al, 2020). Several studies have identified tourism as a driver of the economic growth of any country (Badulescu et al, 2020;Mishra et al, 2011;Swangjang & Kornpiphat, 2021;Tang & Tan, 2015). Innumerable travelers visit different parts of the world to enjoy their leisure time or conduct business activities (Barbhuiya & Chatterjee, 2020;Bonham et al, 2006;Korstanje, 2011;Lepp & Gibson, 2003;Pforr, 2009).…”
Section: Introductionmentioning
confidence: 99%